The Impact of Minimum Wage, Economic Growth, and Unemployment on Poverty Levels in Sumatera - Sihotang, Saut Martua; Hermanto, Bambang Agoes (Formosa Journal of Science and Technology, 2025)
This study analyzes the effect of minimum wage, economic growth, and unemployment rate on the poverty rate in Sumatra Island, Indonesia. The data used is panel data from 10 provinces in Sumatra during the period 2016-2023.The analysis was conducted using the Random Effects Model (REM) method with EViews 12 software. The findings indicate that the minimum wage variable exerts a significant negative influence on the poverty rate, while economic growth demonstrates no substantial effect. Conversely, the unemployment rate exhibits a significant negative impact on poverty.These observations align with the principles of the Wage Efficiency theory and the Social Security Theory, underscoring the significance of augmenting the minimum wage and implementing policies to manage unemployment in efforts to alleviate poverty. However, it is important to note that national economic growth has not been sufficient to meaningfully address the issue of poverty, underscoring the necessity for a more targeted strategy that focuses on enhancing accessibility to education, healthcare, and economic opportunities for disadvantaged populations.